The spatial ecology of chacma baboons (Papio ursinus) in the Cape Peninusula, South Africa: towards improved management and conservation strategies - Hoffman, Tali S (Department of Biological Sciences, 2015)
Competition for space between humans and wildlife is prevalent worldwide. In the Cape Peninsula, South Africa, extensive land transformation has geographically isolated, fragmented and reduced the size of the local chacma baboon population and is perceived to be a major driver of human-baboon conflict. However, no data on baboon landscape use exist to verify this perception. I studied the spatial ecology of this population, identifying baboon land use patterns, determining the drivers of intrapopulation variation in spatial ecology and investigating how spatial variables could inform baboon management efforts to reduce human-baboon conflict.